Aplikasi E-Commerce Hampers Berbasis Mobile pada Toko Sahabat Tegal menggunakan Framework React Native - Khafid Marisuddihan; Vidi Sandi (Switch : Jurnal Sains dan Teknologi Informasi, 2026)
This study aims to design and develop a mobile-based hampers e-commerce application for Toko Sahabat Tegal using the React Native framework. The problem is that the sales process is still conducted manually, making it less effective in managing orders and customer services. The method used is the Software Development Life Cycle (SDLC) with the waterfall model, including requirement analysis, design, implementation, testing, and maintenance. The system is designed using Unified Modeling Language (UML) and Entity Relationship Diagram (ERD), and implemented with Firebase as the backend system. The results show that the application facilitates transaction processes from product selection to payment verification by the admin, and all system features run according to requirements based on black-box testing, all system features run according to the designed requirements. Thus, this application has proven to be suitable for use as a digital solution to support sales transformation at Toko Sahabat Tegal, while simultaneously improving the quality of service to customers in the digital era based on mobile commerce.